Cognitive screening among acute respiratory failure survivors: a cross-sectional evaluation of the Mini-Mental State Examination - Pfoh, Elizabeth R (Crit Care, 2015)
INTRODUCTION: The Mini-Mental State Examination (MMSE) is a common cognitive screening test, but its utility in identifying impairments in survivors of acute respiratory failure is unclear. The purpose of this study was to evaluate MMSE performance versus a concurrently administered detailed neuropsychological test battery in survivors of acute respiratory failure. METHODS: This cross-sectional analysis used data from the ARDSNet Long Term Outcomes Study (ALTOS) and Awakening and Breathing Controlled Trial (ABC). Participants were 242 survivors of acute respiratory failure. The MMSE and detailed neuropsychological tests were administered at 6 and 12 months post-hospital discharge for the ALTOS study, and at hospital discharge, 3 and 12 months for the ABC study. Overall cognitive impairment identified by the MMSE (score <24) was compared to impairments identified by the neuropsychological tests. We also matched orientation, registration, attention, memory and language domains on the MMSE to the corresponding neuropsychological test. Pairwise correlations, sensitivity, specificity, positive and negative predictive values, and agreement were assessed. RESULTS: Agreement between MMSE and neuropsychological tests for overall cognitive impairment was fair (42 to 80%). Specificity was excellent (≥93%), but sensitivity was poor (19 to 37%). Correlations between MMSE domains and corresponding neuropsychological tests were weak to moderate (6 months: r = 0.11 to 0.28; 12 months: r = 0.09 to 0.34). The highest correlation between the MMSE and neuropsychological domains was for attention at 6 months (r = 0.28) and language at 12 months (r = 0.34). CONCLUSIONS: In acute respiratory failure survivors, the MMSE has poor sensitivity in detecting cognitive impairment compared with concurrently administered detailed neuropsychological tests. MMSE results in this population should be interpreted with caution.